Microbiological Investigation of the Effects of Olanzapine with Thymoquinone on the Intestine - Güvenç, Ayşe Nilay; Azirak, Sebile; Taştemir Korkmaz, Deniz; Bilgiç, Sedat; Kocaman, Nevin; Özer, Mehmet Kaya (Adiyaman University, 2022)
The aim of our study is to examine the effect of thymoquinone (TQ) in obese rats induced with the antipsychotic drug olanzapine (OL). Thirty-five female Spraque-Dawley rats were divided into five groups (n = 7): Control, OL (2 mg / kg OL daily), OL + TQ1 (2 mg / kg OL + 20 mg / kg TQ), OL + TQ2 (2 mg / kg OL + 40 mg / kg TQ) and the OL + TQ3 group (2 mg / kg OL + 80 mg / kg TQ). On the 15th day of treatment, intestinal tissue was removed for analysis. It has been found that TQ treatment affects the levels of Firmicutes and Bacteroides at varying rates in the intestinal flora in OL + TQ1, OL + TQ2, and OL + TQ3 groups, and also has a significant role in the apoptotic effect of TQ. In conclusion, with this study, it was determined that the treatment of TQ has a protective property against the side effects of OL. TQ can be an effective treatment method to increase therapeutic effectiveness. © 2022, Adiyaman University. All rights reserved.
Olanzapin ile Timokinon'un Bağırsak Üzerindeki Etkilerinin Mikrobiyolojik Olarak Araştırılması
Keywords: Bacteroides; Firmicutes; Obesity; Olanzapine; Thymoquinone